2013
DOI: 10.1603/en12064
|View full text |Cite
|
Sign up to set email alerts
|

Phenological Variation in the Composition of a Temperate Forest Leaf Tie Community

Abstract: Arthropod communities in an array of temperate ecosystems follow similar phenological patterns of distinct compositional turnovers during the course of a season. The arthropod community inhabiting leaf ties is no exception. Many caterpillars build leaf ties, shelters between overlapping leaves attached together with silk, which are colonized secondarily by a variety of arthropods. We created experimental leaf ties by clipping overlapping leaves together with metal clips. We censused the arthropod community wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…As the season progresses and existing ties become skeletonized from feeding, there may be a lack of suitable sites where uneaten leaves overlap and can be made into additional ties. As a result, the density of occupants inside leaf ties increases over the course of the season (Sigmon & Lill, 2013), as caterpillars become limited by the availability of sites for building shelters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the season progresses and existing ties become skeletonized from feeding, there may be a lack of suitable sites where uneaten leaves overlap and can be made into additional ties. As a result, the density of occupants inside leaf ties increases over the course of the season (Sigmon & Lill, 2013), as caterpillars become limited by the availability of sites for building shelters.…”
Section: Resultsmentioning
confidence: 99%
“…Caterpillars pull together overlapping leaves and fasten them together with silk to create leaf ties, a type of shelter that serves as room and board for the developing insects (Lill & Marquis, 2007). On white oak trees, these ties are secondarily colonized by other leaf-tying caterpillars as well as over 100 species of arthropods, including aphids, psocids, Asiatic oak weevils, rove beetles, thrips, and collembolans (Lill & Marquis, 2004; Sigmon & Lill, 2013). Leaf ties offer many potential advantages to residents, including protection from predators and harsh climatic conditions (Lill & Marquis, 2007), and the presence of leaf ties on a tree has been shown experimentally to increase arthropod abundance and species richness (Lill & Marquis, 2003; Lill & Marquis, 2004; Wang, Marquis & Baer, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are few comparable studies exploring temporal variation in engineering insects. Sigmon & Lill (2013) explored leaf-tying caterpillars and associated arthropod community within ties on oak and birch trees throughout a growing season. They found that caterpillar and arthropod density per tie increased on both tree species as the season progressed, suggesting the intra-annual variation may also be important to consider in the study of engineering insects.…”
Section: Discussionmentioning
confidence: 99%
“…Caterpillars pull together overlapping leaves and fasten them together with silk to create leaf ties, a type of shelter that serves as room and board for the developing insects . On white oak trees, these ties are secondarily colonized by other leaf-tying caterpillars as well as over 100 species of arthropods, including aphids, psocids, Asiatic oak weevils, rove beetles, thrips, and collembolans (Lill andMarquis 2004, Sigmon andLill 2013).…”
Section: Introductionmentioning
confidence: 99%